Dynamic soil-structure interaction current research in China and Switzerland - Zhang, Chuhan; Wolf, John P. (Elsevier, 1998)
Dynamic Soil-structure interaction is one of the major topics in earthquake engineering and soil dynamics since it is closely related to the safety evaluation of many important engineering projects, such as nuclear power plants, to resist earthquakes. In dealing with the analysis of dynamic soil-structure interactions, one of the most difficult tasks is the modeling of unbounded media. To solve this problem, many numerical methods and techniques have been developed. This book summarizes the most recent developments and applications in the field of dynamic soil-structure interaction, both in China and Switzerland. An excellent book for scientists and engineers in civil engineering, structural engineering, geotechnical engineering and earthquake engineering.
Proceedings of the Chinese-Swiss Workshop on Soil-Structure Interaction, held July 14-18, 1997, at Tsinghua University, Beijing.
Keywords: Soil-structure interaction -- Congresses.; Soil-structure interaction -- Research -- China -- Congresses.; Soil-structure interaction -- Research -- Switzerland -- Congresses.; China.; Switzerland.; elektronické knihy; electronic books